A Cost-Benefit Assessment of the Regulatory Policy in Cambodias Mobile Telecommunications Market - LENG, Phirak (Asian Development Policy Review, 2016)
Mobile telecommunications service has exceptionally developed for decades in most part of the world and it recently becomes a widely used technology. Since the development of mobile telecommunications technology evolves in accordance with the regulatory policy and framework, Cambodia is facing some challenges due to the absence of regulations in telecommunications sector. Based on the ADB technical team, the draft of telecoms law is still under the review of the National Assembly and it should be discussed with the public. Therefore, this paper is to assess the costs and benefits of regulatory policies in telecommunications industry incorporating with the consumer perspectives on three factors, the economic efficiency, fairness and stability. With the stated preference method, the fairness is the first significant factor with the coefficient of 38.11% while the economic efficiency at 33.00% and the stability at 28.90%. The fairness is more preferable to be regulated at upper medium level. However, the regulatory intervention for improving the economic efficiency should be at lower medium level while it is required to have high regulatory policies for the development of mobile telecommunications service. In the context of Cambodia, the regulatory policy in mobile telecommunications industry should focus on the fairness, the economic efficiency and the stability respectively.